Analisis peran identitas gender dalam komunikasi kolaboratif di lingkungan akademik - Pakasi, Usman; Qomarrullah, Rif'iy (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Gender identity plays an important role in shaping communication dynamics in academic settings. This study aims to explore the role of gender identity in collaborative communication within student study and discussion groups. This research uses a qualitative approach and draws on literature related to gender, collaborative communication, and higher education. Social construction of gender, gender stereotypes, and communication theory are used as frameworks to analyze the influence of gender identity in the context of group communication. The study population consists of active students. Purposive sampling techniques are used to select participants with diverse gender backgrounds. Data were collected through in-depth interviews and participant observations, and then analyzed using a thematic analysis approach. The results of the analysis show that gender identity affects communication patterns, topic selection, participation, and decision-making in study and discussion groups. The conclusion emphasizes the importance of considering the role of gender identity in designing inclusive and empowering learning environments. The implications of this research for educational practice and future research directions are also discussed.